The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update - Hasan Aif, Ramli; Soeparto, Soeparto (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update